2015
DOI: 10.1371/journal.pone.0124393
|View full text |Cite
|
Sign up to set email alerts
|

When You Have Lived in a Different Culture, Does Returning ‘Home’ Not Feel Like Home? Predictors of Psychological Readjustment to the Heritage Culture

Abstract: Many repatriates find it challenging to readjust to their heritage culture after spending a significant period of time abroad. Research on predictors of readjustment, however, remains limited. The present study in particular investigated the identification of third culture individuals (TCIs) – that is, individuals who spent their formative years outside of their heritage culture - with an abstract, third culture. Our findings demonstrated that TCIs’ identification with the third culture was empirically distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
1
8
1
1
Order By: Relevance
“…Notwithstanding, we found that ST was not predictive of adolescents' psychosocial adjustment (Table 4); moreover, although not significant, there was a marginal positive relation between ST and NA. In addition to provide partial support to previously reported associations between ST and psychiatry problems in adolescents (Consoli et al, 2015) and schizotypy traits in adults (Brambilla et al, 2014), these data indicate that the PeerJ reviewing PDF | (2017:12:22741:1:1:NEW 19 Feb 2018)…”
Section: Discussionsupporting
confidence: 69%
“…Notwithstanding, we found that ST was not predictive of adolescents' psychosocial adjustment (Table 4); moreover, although not significant, there was a marginal positive relation between ST and NA. In addition to provide partial support to previously reported associations between ST and psychiatry problems in adolescents (Consoli et al, 2015) and schizotypy traits in adults (Brambilla et al, 2014), these data indicate that the PeerJ reviewing PDF | (2017:12:22741:1:1:NEW 19 Feb 2018)…”
Section: Discussionsupporting
confidence: 69%
“…First, participants completed a modified version of the Vancouver Index of Acculturation (VIA; Ryder, Alden, & Paulhus, 2000), translated into Dutch, which measures the extent to which they identify with mainstream Dutch culture (α = .79) and with their religion (α = .86). Previous studies have shown that the VIA can be used as a reliable measure of cultural identification (e.g., Altweck & Marshall, 2015; Cheung, Chudek, & Heine, 2011). Participants indicated to what extent they agreed with 20 statements on a 9-point scale, ranging from 1 ( disagree ) to 9 ( agree ).…”
Section: Methodsmentioning
confidence: 99%
“…In doing so, they need to rely on and trust in what we can call "limit objects, " which can help them as a bridge between both cultures; these objects "can be adapted to both cultures according to the individual's needs while keeping their own identity along the way" (Star & Griesemer as cited in Akkermman & Bakker, 2011, p. 134). The process of transferring from one culture to the other results in what we can call "third culture, " which creates a learning environment where students share aspects of the target culture in a lifestyle they had in their home culture (Altweck & Marshall, 2015;Wolcott, 2010). What is more important, students need to keep an active role and a positive attitude (Bennett, 2004;Carini, Kuh, & Klein, 2006;Carlson & Widaman, 1988;Engberg, Jourian, & Davidson, 2016;Félix-Brasdefer & Haster-Barker, 2015;Trilokekar & Rasmi, 2011).…”
Section: Cultural Understandingmentioning
confidence: 99%